Early Childhood Intervention in North Macedonia – Parents’ Perspective (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2024)
Early childhood intervention (ECI) should focus on building strong relationships with families, as this family-centered approach leads to improved developmental outcomes for children. This study examines ECI and support systems in the Republic of North Macedonia from the perspective of families of children with developmental delays or disabilities. A descriptive method was used, suitable for describing individuals, processes or situations as they unfold in nature, with no manipulation of variables. The research included a sample of 78 parents of children with developmental delays or disabilities.The findings indicate that when at-risk factors or disabilities are identified shortly after birth, ECI tends to be quick and efficient. Most services (71.4%) are provided in ECI centers, while 28.6% of families receive services at home. Some 53.8% of families reported covering the costs of all ECI services. By the age of three, 43.7% of children had been detected, diagnosed, and received some form of stimulation services or early rehabilitation treatment. The insights gained from this study may also be applicable in other countries with similar ECI systems.
Keywords: Early childhood intervention; developmental delay; disability; family-centered intervention